Rolling out COVID-19 vaccine: half the battle won - Alishba Adnan; Chanchal Maheshwari; Syed Muhammad Ashraf Jahangeer (Journal of the Pakistan Medical Association, 2021)
According to the World Bank forecast COVID19 economic consequences have been estimated as the deepest recession since the Second World War. To date COVID19 has claimed 1.4 million lives, leaving millions in varying levels of morbidity and emerges as a bigger problem in the high income than in the low middle income countries. The only hope to put a stop to this monster and go back to the normal is the man’s old friend, the vaccines. Extraordinary circumstances require extraordinary measures and we have seen that the development of vaccines which was usually thought as a years of business is being prepared and ready to be rolled out under ten months of concentric efforts. A certain percentage of adverse effects are expected from any medication and the same is true for vaccines. However even within the expected numbers of any untoward effects from vaccines, the same are highlighted and become under media limelight for no scientific reason. In this regard manageing mthe mass media is imperative. In the recent history of infections and vaccines, the world has seen both causal and spurious adverse relationships claimed to be associated with vaccines. Whatever the truth was, news of vaccines causing adverse reactions can not only affect the uptake of the very vaccine itself, but can also avert people to go for other routine vaccinations. In the low and middle income countries of the world this could prove as an impending community health disaster. In a country like the UK the Wakefield reports caused decline in the vaccine uptake and a surge in the infections, so what worse we can be expected in other parts of the world. Considering the tight rope of a newly developed vaccine administration in the first stage, ‘the first few thousands’ in the population would be a make or break situation, specially in the low middle income countries where rumors spread faster than anything. In the second stage, targeting a bigger population for vaccine delivery, diligent planning at both macro and micro levels would be required to avoid problems related to vaccine storage, safe delivery, administration and follow up of the vaccine receivers. This pandemic provided us with an opportunity to uncover our potential in a time constraint Global health crisis. The precious achievements of scientists and vaccine manufacturers in this regard must be capitalized upon and be secured from mishaps and mismanagement. Continuous...